Management of Resistant Population of Spodoptera litura with New Molecules of Insecticides - Aruna Sri, I; Madhumathi, T; Rao, P Arjuna (Indian Journal of Plant Protection, 2020)
In the present study, the toxicity of new molecules of insecticides was tested against resistant Guntur strain of Spodoptera litura during Kharif 2007 and 2008. Among the new insecticides, emamectin benzoate was found to be the best with highest relative toxicity of 34.2, 40.4, 52.8 and 59.0 times in Kharif 2007, and 37.4, 7.9, 60.0 and 73.4 times in Kharif 2008 compared to chlorpyriphos, quinalphos, cypermethrin and methomyl respectively. Pyridalyl was the next best which showed better toxicity than test insecticides. indoxacarb was the third best in relative toxicity followed by flubendiamide. Among the new insecticides, lambda cyhalothrin, novaluron and spinosad showed poor efficacy against the resistant Guntur strain of S. litura.